The miRNA landscape of colorectal polyps. Issue 5 (1st February 2017) - Slattery, Martha L.; Herrick, Jennifer S.; Wolff, Roger K.; Mullany, Lila E.; Stevens, John R.; Samowitz, Wade
Abstract : The genomic landscape of adenomas and polyps may help define disease pathways. Expression of miRNAs in adenomas and polyps may importantly contribute to these pathways. We evaluated miRNA expression in 293 polyp‐normal colorectal mucosa pairs. Polyps were classified as either adenomatous polyp (AD), hyperplastic polyp (HP), or sessile serrated polyp (SSP). We compared these miRNA expression profiles in polyps to miRNA expression in microsatellite unstable (MSI) and stable (MSS) tumors. A False Discovery Rate of 0.05 based on Benjamini and Hochberg was used to adjust for multiple comparisons. There were 70 miRNAs with differential expression by polyp type with a fold change <0.75 or >1.34 after adjusting for multiple comparisons. The major differences in miRNA expression were observed between AD and SSP and AD and HP, with few differences in expression noted for SSP and HP. AD polyps were more likely to be upregulated from normal colonic mucosa, while SSP and HP were more likely to be downregulated from normal colonic mucosa. MiRNA expression in the SSP and HP tumors almost uniformly go in opposite directions from the MSS tumor miRNA expression and was mixed with MSI tumors. We conclude that different types of polyps have unique miRNA expression profiles. © 2017 Wiley Periodicals, Inc.